Pelaksanaan KTSP Pada MTsN Malang III Kabupaten Malang - Wahab Wahab (Balai Penelitian dan Pengembangan Agama Semarang, 2009)
his study aims to identify - and analyze the implementation KTSP-inhibiting factor in supporting MTsN III Malang Regency. Beforeimplementing MTsN KTSP make preparations mature enough and stable.Implementation of KTSP in MTsN III Malang running smoothly, procedural,and in accordance with the laws, regulations and guidance from BSNP.As an indicator of KTSP implementation can be ascertained from studentachievement in the UN in 2008 the average value of 7.18 and in 2009 theaverage value of 8.75. Some of non-academic and academic achievementsof the various competitions from local, regional, national and evenASEAN succeed achieved by MTsN III Malang. Factors supporting theimplementation of KTPS MTsN III Malang can be known from the ethos,dedication, loyalty, and professionalism of each school functionary (Head,Deputy Head, teachers, staff of the General Affair, and student input). Whileblocking factor has not fully have ideal classrooms (20-30 students perclass).Keywords: KTSP, Madrasah, Implementation KTSP.